Confirmatory factor analyses of the Mandarin Chinese version of the perceived stressors in intensive care units among healthcare professionals - Gao, Yonge; Chen, Xia; Zhang, Shuang; Yang, Jiawei; Liu, Rui; Moyle, Wendy; Pu, Lihui; Shen, Wei (Frontiers in Public Health, 2025)
BackgroundThe Perceived Stressors in Intensive Care Units (PS-ICU) scale was designed to assess both general and occupational stressors experienced by healthcare professionals (HCPs) under normal circumstances. It has demonstrated good psychometric properties in three languages: French, Spanish, and Italian. The aim of the present study was to translate the scale into Mandarin Chinese and to examine its construct validity and reliability.MethodsThis study was conducted from April 2022 to October 2023. In phase I, the scale was translated into Mandarin Chinese following the Cross-cultural adaptation guidelines and reviewed by expert panels. In phase II, the reliability and validation were tested by 530 HCPs working in tertiary grade A hospitals from two provinces (Shandong and Sichuan) in China. Fifty participants were contacted to evaluate the test–retest reliability and underwent a follow-up investigation 2 weeks after completing the initial online survey.ResultsThe content validity ratio for the 50 questions varied between 0.8 and 1, with every item having S-CVI values exceeding 0.92. After removing 4 items, the Exploratory Factor Analysis (EFA) results revealed six factors. Confirmatory Factor Analysis (CFA) affirmed construct homogeneity, comprising of (1) lack of fit with families and the organizational functioning, (2) emotional load associated with patient and family, (3) difficulties associated with teamwork, (4) issues associated with workload and human resource management, (5) issues associated with complex/at-risk situations and skill, (6) and suboptimal care situations. The comprehensive scale displayed strong internal consistency (the total Cronbach’s α = 0.96) and showed high 2-week test–retest reliability (Person’s r = 0.95). The Job Content Questionnaire (JCQ) was employed to assess the criterion-related validity, alongside with the Maslach Burnout Inventory-Hunman Services Survey (MBI-HSS), which revealed either positive or negative associations between PS-ICU and these measures.ConclusionThe final 46-item Mandarin Chinese version of the PS-ICU scale is reliable and valid for evaluating perceived stressors among HCPs under normal ICU conditions. It may significantly identify perceived stressors in the ICU providing a foundation for focused intervention research.